Identification of integrative and conjugative elements in pathogenic and commensal Neisseriaceae species via genomic distributions of DNA uptake sequence dialects. Issue 5 (4th May 2020) - Hughes-Games, Alex; Roberts, Adam P.; Davis, Sean A.; Hill, Darryl J.
Abstract : Mobile genetic elements (MGEs) are key factors responsible for dissemination of virulence determinants and antimicrobial-resistance genes amongst pathogenic bacteria. Conjugative MGEs are notable for their high gene loads donated per transfer event, broad host ranges and phylogenetic ubiquity amongst prokaryotes, with the subclass of chromosomally inserted integrative and conjugative elements (ICEs) being particularly abundant. The focus on a small number of model systems has biased the study of ICEs towards those conferring readily selectable phenotypes to host cells, whereas the identification and characterization of integrated cryptic elements remains challenging. Even though antimicrobial resistance and horizontally acquired virulence genes are major factors aggravating neisserial infection, conjugative MGEs of Neisseria gonorrhoeae and Neisseria meningitidis remain poorly characterized. Using a phenotype-independent approach based on atypical distributions of DNA uptake sequences (DUSs) in MGEs relative to the chromosomal background, we have identified two groups of chromosomally integrated conjugative elements in Neisseria : one found almost exclusively in pathogenic species possibly deriving from the genus Kingella, the other belonging to a group of Neisseria mucosa -like commensals. The former element appears to enable transfer of traditionally gonococcal-specific loci such as the virulence-associated toxin–antitoxin system fitAB to N. meningitidis chromosomes, whilst the circular form of the latter possesses a unique attachment site ( attP ) sequence seemingly adapted to exploit DUS motifs as chromosomal integration sites. In addition to validating the use of DUS distributions in Neisseriaceae MGE identification, the >170 identified ICE sequences provide a valuable resource for future studies of ICE evolution and host adaptation.